A Comparative Evaluation on the Effect of Zinc-Probiotic Combination and Probiotic Therapy Alone in Paediatric Acute Diarrhoea (The Planet, 2023)
Introduction:Diarrhea is one of the main causes of childhood disability and death worldwide, resulting in 5-10 million deaths annually. It is a major public health problem in developing countries like Bangladesh. It was observed that probiotics alleviated diarrhea in 3-4 days.Methods and materials:This study examined the effects of zinc and probiotics in combination for the management of acute diarrhea in children. 50 children were divided into two groups, where Group I received a combination of zinc and probiotics and Group II received probiotics alone. Result: Group I had a mean age of 18.22±11.78 months and 60.0% of patients were male, with a mean weight of 10.92±3.6 kg. 26.0% had mild malnutrition and 28.0% had fever. 64.0% had a volume of stool/purging 7-13, and the mean hospital stay was 3.46±1.02. Group II had a mean age of 12.66±7.87 months and 44.0% were male, with a mean weight of 9.26±2 kg. 24.0% had mild malnutrition and 24.0% had fever. 72.0% had a volume of stool/purging 7-13, and the mean hospital stay was 3.99±1.13. Overall, 44.0% of patients had a number of vomitus
Keywords: Diarrhea; childhood disability; probiotics; zinc supplementation; diarrheal episodes in children